Upaya Peningkatan Mutu Pembelajaran IPA Melalui Laboratorium Di MTS Uswatun Hasanah Bandung Barat - Widianti, Cicih; Murdani, Denny (Jurnal Online Manajemen ELPEI, 2024)
This research aims to develop teaching materials and learning methods through laboratories in the context of improving the quality of science learning at Uswatun Hasanah Islamic Junior High School Padalarang, West Bandung. The research method used is a qualitative approach using interviews, observation and documentation as data collection techniques. The research was conducted involving school principals, science teachers, and students of Uswatun Hasanah Islamic Junior High School. The research results show that: 1) The development of teaching materials and learning methods through laboratories has a positive impact on the science learning process. 2) Teachers and students say that using laboratories as a learning tool can improve students’ understanding of concepts, practical skills and interest in related subjects. Apart from that, through laboratories, students can also develop cooperation, problem solving and critical thinking skills. 3) The school principal and science teacher at Uswatun Hasanah Islamic Junior High School also said that school operational management such as management of facilities and infrastructure, especially laboratories, needs to be carried out considering that this school does not yet have a laboratory as a supporting component in science learning activities. This research also reveals several challenges faced in developing and implementing teaching materials and learning methods through laboratories, such as limited resources (financial, materials and tools) and limited building space. However, with the right support, these challenges can likely be overcome and the benefits from procuring and using laboratories can be maximized.